Investigating the association between inpatient stroke therapy and disability, destination on discharge, length of stay and mortality: a prospective cohort study using the Sentinel Stroke National Audit Programme. Issue 4 (1st April 2022) - Gittins, Matthew; Lugo-Palacios, David Gibran; Vail, Andy; Bowen, Audrey; Paley, Lizz; Bray, Benjamin; Gannon, Brenda; Tyson, Sarah
Abstract : Objective: 'More is better' is a recognised mantra within stroke therapy, however, this has been developed in patients receiving long term rehabilitation. We investigated the relationship between amount of therapy received (from therapists and psychologists) and key patient outcomes during inpatient care. Design: A secondary analysis of data from a prospective cohort study was performed. Multilevel mixed models adjusting for measured confounders (eg, severity), explored the relationship between therapy dose (average minutes per day of stay) and outcomes (disability, length of stay, home at discharge and mortality). Therapy was explored using simple linear terms and flexible natural cubic splines to allow for more complex relationships. Setting: Data from the Sentinel Stroke National Audit Programme, covering England, Wales and Northern Ireland between July 2013 and July 2015 contained 94 905 adults with a stroke and still an inpatient after 72 hours. These patients received 92% (physiotherapy), 88% (occupational therapy), 57% (speech and language therapy) and 5% (clinical psychology), respectively. Results: The average amount of therapy, for individual and 'any' therapy combined per day of stay was low. Overall, 41% were discharged with an 'independent' modified Rankin Scale (≤2), 14% died, 44% were discharged home, and the median length of stay was 16 days. We observed complex relationships between amount of therapy received and outcomes. An additional minute of 'any' therapy, occupational therapy, speech and language therapy and clinical psychology was associated with improved outcomes. Conversely, more physiotherapy was also associated with lower mortality and shorter length of stay, but also lower independence and discharge home. Conclusions: Our findings suggest for stroke inpatients requiring therapy, 'More is better' may be overly simplistic. Strong limitations associated with analysis of routine data restrict further robust investigation of the therapy–response relationship. Robust prospective work is urgently needed to further investigate the relationships observed here.